Fetal growth restriction caused by MIMT1 deletion alters brain transcriptome in cattle. Issue 7 (28th May 2013) - Venhoranta, Heli; Bauersachs, Stefan; Taponen, Juhani; Lohi, Hannes; Taira, Tomi; Andersson, Magnus; Kind, Alexander; Schnieke, Angelika; Flisikowski, Krzysztof
Abstract: We examined levels of gene expression in the brains of bovine fetuses carrying a truncated MIMT1 allele, MIMT1 Del, shown to cause late abortion and stillbirth as a result of fetal growth restriction. MIMT1 is a non‐protein coding gene that forms part of the imprinted PEG3 (paternally expressed gene 3) domain. Microarray analysis of brain cortex samples from mid‐gestation MIMT1 Del/WT bovine fetuses and wild‐type siblings was performed to study the effect of fetal growth restriction on brain gene expression. Statistical analysis revealed 134 genes with increased mRNA levels and 22 with reduced levels in MIMT1 Del/WT fetuses. Gene set enrichment analysis identified a relatively small number of significant functional clusters representing three major biological processes: response to oxidative stress, angiogenesis, and epithelial cell proliferation. Gene expression microarray analyses identified increased expression of VIPR2, HTRA1, S100A4 and MYH8 in fetuses carrying the deletion and decreased expression of DRD2, ADAM18, miR345, ZNF585A . ADAM18, DRD2 and S100A4 are known to be involved in prenatal brain development. ZNF585A, miR‐345, VIPR2, HTRA1, and MYH8 are known to be involved in cell growth and differentiation, but any role in neural developmental has yet to be elucidated.